EGFL6 Promotes Breast Cancer by Simultaneously Enhancing Cancer Cell Metastasis and Stimulating Tumor Angiogenesis - An, Jingnan (Oncogene, 2018)
EGFL6, a member of the EGF like superfamily, plays an important role during embryonic development and has been implicated in promotion of tumor angiogenesis without affecting wound healing. There is very little known about the function of EGFL6 in cancer cells. Here, we investigated whether EGFL6 plays a direct role in cancer cells in addition to the promotion of tumor angiogenesis. Our study showed that EGFL6 promoted epithelial mesenchymal transition (EMT) and stemness of breast cancer cells and increased cell migration and invasion in cell culture studies. We also found that EGFL6 reduced apoptotic signaling in cancer cells and promoted tumor growth in vivo. Importantly, expression of EGFL6 in cancer cells and tumor endothelial cells not only increased tumor angiogenesis but also promoted migration of cancer cells. Such dual engagement of cancer and stromal cells suggests crosstalk mediated by EGFL6 in the tumor microenvironment. Blockade of EGFL6 using our novel anti-EGFL6 monoclonal antibody significantly reduced cancer cell migration, tumor angiogenesis and tumor growth in mouse xenograft tumor models. Silencing EGFL6 mRNA by shRNA transfection of cancer cells also significantly reduced cancer cell migration, tumor angiogenesis, and tumor growth in mouse xenograft tumor models. Taken together, the results of this study indicate that targeting EGFL6 is a unique strategy for inhibiting both cancer cell metastasis and tumor angiogenesis.